Case Report: Multiple types of arrhythmias in a late-confirmed Danon disease - Wang, Nan; Cao, Yu; Wang, Jie; Zhang, Qing (Frontiers in Cardiovascular Medicine, 2024)
Introduction: Danon disease is an X-linked disorder caused by pathogenic variants in the LAMP2 genes that is typically characterized by the triad of hypertrophic cardiomyopathy, myopathy, and intellectual disability. However, a lot of patients might not have the typical presentation, especially in the early stage. Electrocardiogram (ECG) abnormalities can be found in almost all patients, with the most common being Wolff-Parkinson-White (WPW) syndrome. We reported a 51-year-old woman with multiple types of arrhythmias in three decades who was diagnosed with Danon disease late by genetic testing.A 51-year-old woman who presented with intermittent palpitations for 36 years was admitted due to hemodynamically stable ventricular tachycardia (VT).Her past medical history was significant for multiple arrhythmias and ECG abnormalities in her 30s and 40s, including WPW syndrome with paroxysmal supraventricular tachycardia, paroxysmal atrial flutter, atrial fibrillation, ventricular tachycardia, and complete left bundle branch block. She denied any family history of cardiovascular disease or sudden death. The vital signs on arrival were unremarkable.Cardiovascular magnetic resonance (CMR) imaging showed left ventricular enlargement and late gadolinium enhancement (LGE) in the anterior, inferior, and lateral walls. Subsequently, the whole exome sequencing (WES) gene testing revealed a pathogenic heterozygous variant in the lysosome-associated membrane protein 2 (LAMP2) gene (c.696T>A; p.Cys232Ter), which confirmed the diagnosis of Danon disease.Genetic testing should be considered in patients who display multiple arrhythmias with LV structural abnormalities of unknown reasons for a possible Danon disease.